TINJAUAN YURIDIS TERHADAP TINDAK PIDANA PEMBUNUHAN BERENCANA YANG DILAKUKAN SEPASANG KEKASIH DI KOTA BAUBAU : STUDI PUTUSAN NO 325/PID.B/2014/PN.BAU - Ali Mustafa La Ode; Alfaj’ri (Jurnal Ilmu Hukum Kanturuna Wolio, 2026)
This study examines a premeditated murder case committed by a couple in Baubau City, citing judgment number 325/Pid.B/2014/PN.Bau of the Baubau District Court. The phenomenon of premeditated murder is of particular importance because it demonstrates the highest degree of culpability in criminal law, with the element of premeditation constituting the primary distinction from ordinary murder. This study employed normative legal research methods with a legal and case-based approach, supported by primary data in the form of copies of court judgments and secondary data from criminal law literature. The results indicate that the judge correctly applied Article 340 of the Criminal Code in conjunction with Article 55, paragraph (1), point 1 of the Criminal Code in the ruling. The elements of the crime, from intent and planning to the involvement of each defendant, were legally and convincingly proven in court. The judge's considerations also reflect a balance between legal and non-legal aspects, by considering both aggravating factors (such as careful planning and the impact on the victim's family) and mitigating factors (the defendant's polite attitude and confession). This study emphasizes the importance of applying the principles of nullum crimen sine lege and nulla poena sine lege in criminal law enforcement. This ruling not only provides legal certainty and a deterrent effect for perpetrators, but also has an educational and preventive dimension for society, by reminding that serious crimes such as premeditated murder are punished severely under the law.